Two new species of marsupial tree-frogs genus Gastrotheca Fitzinger, 1843 (Anura, Hemiphractidae) from the Brazilian Atlantic Forest - Teixeira Jr., Mauro; Dal Vechio, Francisco; Recoder, Renato Sousa; Carnaval, Ana Carolina; Strangas, Maria; Damasceno, Roberta Pacheco; de Sena, Marco Aurélio; Rodrigues, Miguel Trefaut (Zootaxa, 2012)
Two new species of Gastrotheca are described from northeastern Minas Gerais and southern Bahia, in the Atlantic Forestof Brazil. Data on morphology, calls, mitochondrial, and nuclear DNA are provided. Allied to G. fissipes and G.megacephala, the new taxa provide evidence for a higher diversity of species of Gastrotheca than previously thought atthe Atlantic Forest. The data also suggest that G. pulchra, another Atlantic Forest taxon, is more closely related to non-Atlantic Forest species than to the remaining analyzed Brazilian Gastrotheca species. This implies that the Gastrotheca at the Brazilian coastal forests have at least two independent origins.